Neurosurgical Management of a Giant Parasagittal Meningioma in a Patient with Neurofibromatosis Type 2: A Case Report - Aguilar, Luis (2025)
Parasagittal meningiomas are intracranial tumors that develop along the superior sagittal sinus. Although they are generally benign, their proximity to vital vascular structures poses significant challenges for surgical management. In patients with neurofibromatosis type 2 (NF2), an autosomal dominant genetic disorder, there is a high predisposition to develop multiple tumors in the central nervous system, including meningiomas and schwannomas. The report discusses a 23-year-old woman with a family history of NF2 who presented with a large parasagittal meningioma and bilateral schwannomas, along with symptoms such as headaches, hearing loss, vertigo, and seizures. MRI revealed a right frontoparietal meningioma invading the superior sagittal sinus. Successful craniotomy and resection showed a poorly vascularized meningioma invading the sagittal sinus. This case highlights the surgical difficulties associated with sagittal sinus meningioma invasion and emphasizes the importance of multidisciplinary care and long-term follow-up due to the high risk of tumor recurrence in NF2 patients.